The language of medicine - Chabner, Davi-Ellen (​Elsevier, 2014)
The Language of Medicine, 10th Edition! By presenting medical terms within the context of the body’s anatomy and physiology, and in health and disease, this proven resource makes it easy to learn a working medical vocabulary built on the most frequently encountered prefixes, suffixes, and combining forms. Practical exercises and case studies demonstrate how medical terms are used in practice. Add an engaging student Evolve website with medical animations and videos, word games, flash cards, and more, and you’ll be ready to communicate confidently in the clinical setting and succeed in your healthcare career.